Diagnostic and prognostic value of cancer stem cell marker CD44 and soluble CD44 in the peripheral Blood of patients with oral Squamous cell carcinoma - Khamis, Aya K.; Fouad, Hamed A.; Raslan, Hanaa S.; Fata, Mohamed M.; Fayad, Amira I. (Open Science Journal, 2017)
Background Head and neck cancer is a major health problem. Recent studies on the pathobiology of oral squamous cell carcinoma (OSCC) have led to the discovery of a small population of cancer cells with a consistent behavior with the features of cancer stem cells (CSCs). CSCs are required and responsible for initiation, maintenance and recurrence of disease. Molecular markers are commonly used for the identification of CSCs. CD44 is the most reported CSC marker in OSCC. The aim of the study was to evaluate and correlate the expression of CD44 in different histopathological grades of OSCC, as well as to assess the diagnostic and prognostic value of soluble CD44 (CD44sol) in peripheral blood of patients. Materials and methods Fifteen patients with OSCC were included; biopsies were histologically evaluated using haematoxylin and eosin. Serial sections were immunohistochemically stained by monoclonal antibody to CD44. The intensity of immunostaining of CD44 was calculated. Enzyme-linked immunosorbent assay (ELISA) method was used to determine the concentration of CD44sol in the blood serum. Results All grades of OSCC showed membranous immunosignaling of CD44. The well, moderately and poorly differentiated OSCC cases showed weak, moderate and intense positive membranous immunosignaling of CD44 respectively. CD44sol levels were significantly higher in OSCC patients than they were in control groups. Soluble CD44 serum levels were significantly higher in poorly differentiated than they were in moderately and well differentiated. Conclusion CSCs detection in fixed human tissue and CD44sol detection in peripheral blood using ELISA seemed to be a promising method and may have a diagnostic and prognostic value in management of OSCC.